PENGARUH KOMPETENSI, DISIPLIN KERJA DAN PELATIHAN TERHADAP KINERJA PEGAWAI PADA BADAN PUSAT STATISTIK PROVINSI RIAU - ,Anggia Paramitha, Ina Sri Wijayanti Soleha ,Rosnelly Roesdy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The Central Statistics Agency of Riau Province is one of the representative institutions of the Central Statistics Agency  in the regions which has the main task of providing basic statistical data in accordance with the provisions of applicable laws and regulations. This research was conducted at the Central Bureau of Statistics Jalan Patimurra No. 12 Pekanbaru, Riau. The purpose of this study was to determine the effect of competence, work discipline and training on employee performance. This type of research is quantitative. The population in this study were 82 employees of the Central Statistics Agency of Riau province. The sample in this study was the entire population, amounting to 82 people. The sampling method used in this study is non-probability sampling. This study uses multiple linear regression analysis using SPSS 23. The results of this study indicate that competence has a positive and significant effect on performance, work discipline has a positive and significant effect on performance, and the training variable has a positive and significant effect on performance. Meanwhile, simultaneously the variables of competence, work discipline and training have a positive and significant effect on employee performance. Keywords: Employee Performance, Competence, Work Discipline, Training.